2
$\begingroup$

How can I balance this reaction using the algebraic method?

$$\ce{K4Fe(CN)6 + KMnO4 + H2SO4 + H2SO4 -> KHSO4 + Fe2(SO4)3 + MnSO4 + HNO3 + CO2 + H2O}$$

My solution:

$$\ce{a K4Fe(CN)6 + b KMnO4 + c H2SO4 -> d KHSO4 + e Fe2(SO4)3 + f MnSO4 + g HNO3 + h CO2 + i H2O}$$

$\ce{K}{:~} 4a + b = d$
$\ce{Fe}{:~} a = 2e$
$\ce{C}{:~} 6a = h$
$\ce{N}{:~} 6a = g$
$\ce{Mn}{:~} b = f$
$\ce{O}{:~} 4b + 4c = 4d + 12e + 4f + 3g + 2h + i$
$\ce{H}{:~} 2c = d + g + 2i$
$\ce{S}{:~} c = d + 3e + f$

I couldn't solve further than that.

$\endgroup$
  • 1
    $\begingroup$ I will just point it out - although you require the algebraic method - that the redox method instead is much easier than this. $\endgroup$ – Gaurang Tandon Jun 14 '18 at 11:18
4
$\begingroup$

You are lucky. From time to time, I take on a challenge like this, just to see if I can still do it. But normally, we expect that you show some effort yourself. See our homework policy.

We start off with some mathematics.

(1) $4a + b = d$
(2) $a = 2e$
(3) $6a = h$
(4) $6a = g$
(5) $b = f$
(6) $4b + 4c = 4d + 12e + 4f + 3g + 2h + i$
(7) $2c = d + g + 2i$
(8) $c = d + 3e + f$

and rewrite this in the "equals zero" form.

(1) $0 = 4a + b - d$
(2) $0 = a - 2e$
(3) $0 = 6a - h$
(4) $0 = 6a - g$
(5) $0 = b - f$
(6) $0 = 4b + 4c - 4d - 12e - 4f - 3g - 2h - i$
(7) $0 = 2c - d - g - 2i$
(8) $0 = c - d - 3e - f$

I fill this in a table. (I could have done this right from the original chemical equation.)

     a   b   c   d   e   f   g   h   i
(1)  4   1      -1 
(2)  1              -2
(3)  6                          -1
(4)  6                      -1
(5)      1              -1
(6)      4   4  -4 -12  -4  -3  -2  -1
(7)          2  -1          -1      -2 
(8)          1  -1  -3  -1

Now, (2) to (5) look simple enough to do some replacements. I start with (2) where $a = 2e$. In the first line, we replace $4a$ by $8e$ and so forth.

     a   b   c   d   e   f   g   h   i
(1)  0   1      -1  0+8
(2)  0             -2+2
(3)  0              0+12        -1
(4)  0              0+12    -1
(5)      1              -1
(6)      4   4  -4 -12  -4  -3  -2  -1
(7)          2  -1          -1      -2 
(8)          1  -1  -3  -1

We got rid of $a$, (2) is cancelled out. (5) allows us to get rid of $b$ via $b=f$.

     a   b   c   d   e   f   g   h   i
(1)      0      -1   8  0+1
(3)                 12          -1
(4)                 12      -1
(5)      0             -1+1
(6)      0   4  -4 -12 -4+4 -3  -2  -1
(7)          2  -1          -1      -2 
(8)          1  -1  -3  -1

Let's use (3) and (4) to remove $g=12e$ and $h=12e$.

     a   b   c   d   e   f   g   h   i
(1)             -1   8   1
(3)                12-12         0
(4)                12-12     0
(6)          4 -4 -12-36-24  0   0  -1
(7)          2  -1  0-12     0      -2 
(8)          1  -1  -3  -1

i.e.

     a   b   c   d   e   f   g   h   i
(1)             -1   8   1
(6)          4  -4 -72              -1
(7)          2  -1 -12              -2 
(8)          1  -1  -3  -1

Now we take (1) with $d = 8e+1f$

     a   b   c   d   e   f   g   h   i
(6)          4     -104 -4          -1
(7)          2      -20 -1          -2 
(8)          1      -11 -2

Now we take (8) with $c = 11e+2f$

     a   b   c   d   e   f   g   h   i
(6)                -60   4          -1
(7)                  2   3          -2 

One last step with (6) $i=-60e+4f$

     a   b   c   d   e   f   g   h   i
(7)                122  -5

That is $f=122e/5$

We cannot solve that further with mathematics. There is an infinite number of possible results. We need just one solution, so we guess one number. $e=5$ seems good so that we get a nice $f$. Now, from the many equations we had above, we search some that fit.

$e = 5$
$a = 2e = 10$
$f = 122e/5 = 122$
$g = 12e = 60$
$h = 12e = 60$
$b = f = 122$
$c = 11e+2f = 299$
$d = 4a+b = 162$
$i = -60e+4f = 188$

$\endgroup$
3
$\begingroup$

Now all you have to do is variable substitution, which is kinda tedious since it's such a large equation. Remember that solutions are defined up to multiplying everything by a constant factor, so we might as well pick

  • $a = 2$ (this guess is inspired by the equation for $\ce{Fe}$)
  • $\ce{Fe}{:~} e = 1$
  • $\ce{C}{:~} h = 12$
  • $\ce{N}{:~} g = 12$
  • Because $\ce{Mn}{:~} b = f$, we can rewrite $\ce{O}$ as $4c = 4d + 12e + 3g + 2h + i$
  • Subtract 4 times $\ce{S}$, and we get $0 = -4f + 3g + 2h + i$, so $4f = 60 + i$ (call this $\ce{O}'$)
  • Now rewrite everything in terms of $b$:
    • $\ce{K}{:~} 8 + b = d$, so $d = b + 8$
    • $\ce{Mn}{:~} f = b$
    • $\ce{O}'{:~} 4b = 60 + i$, so $i = 4b - 60$
    • $\ce{S}{:~} c = (b + 8) + 3 + b = 2b + 11$
    • $\ce{H}{:~} 2(2b + 11) = b + 8 + 12 + 2(4b - 60)$, so $4b + 22 = 9b - 100$, so $5b = 122$ and $b = 122/5$. This is a bit unfortunate since later on we have to multiply all variables by 5.
  • We now have $a=2$, $b=122/5$, $c=299/5$, $d=162/5$, $e=1$, $f=122/5$, $g=12$, $h=12$ and $i=188/5$.
  • By multiplying everything by 5 we get the final solution:
    • $a = 10$
    • $b = 122$
    • $c = 299$
    • $d = 162$
    • $e = 5$
    • $f = 122$
    • $g = 60$
    • $h = 60$
    • $i = 188$

You can check that these figures will make the equation balanced.

$\endgroup$

Your Answer

By clicking "Post Your Answer", you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.